Pengaruh Memory Training Permainan Anagram terhadap Kognitif Lansia di Panti Jompo Sumber, Surakarta - Prayoga, Dimas; Puspitosari, Aniek (Jurnal Terapi Wicara dan Bahasa, 2024)
Background: One of the problems experienced by the elderly is experiencing a decrease in cognitive abilities such as difficulty remembering, retrieving new information, focusing, making decisions and various aspects such as orientation, visual spatial, memory and language. The problem of cognitive decline will develop into dementia and will affect functional abilities and reduce the quality of life of the elderly. Prevention of cognitive decline in the elderly can be done with cognitive interventions in the form of memory training anagram games. Objectives: This study aims to determine the effect of anagram game memory training on cognitive abilities in the elderly. Methods: This study used a pre-experimental one group pre-test and post-test method with a total sample of 42 elderly people at Aisyiyah Sumber Solo Nursing Home. The research instrument used the Indonesian version of the Montreal Cogntive Assessment (MoCA-Ina). Three stages of the anagram game were given each intervention based on the research module that had been prepared. The data analysis method uses paired t-test with the previous stage, namely data normality test with Shapiro Wilk. Results: The paired t-test results showed that the sig value was <0.05. An increase in moCA-Ina scores occurred after being given anagram game memory training intervention (mean difference 2.48). Memory training of anagram games affects the cognitive abilities of the elderly at Aisyiyah Sumber Solo Nursing Home (????=0.000). The research sample was entirely female, 76.2% dominated by the early elderly age group, 90.5% low-level education. Conclusion: This study shows that memory training intervention in the form of anagram games has a significant effect on the cognitive abilities of the elderly. Keywords: Dementia, Memory, MoCA-Ina, Cognitive games